2012
DOI: 10.1007/s00445-012-0601-5
|View full text |Cite
|
Sign up to set email alerts
|

Using dissolved H2O in rhyolitic glasses to estimate palaeo-ice thickness during a subglacial eruption at Bláhnúkur (Torfajökull, Iceland)

Abstract: The last decade has seen the refinement of a technique for reconstructing palaeo-ice thicknesses based on using the retained H 2 O and CO 2 content in glassy eruptive deposits to infer quenching pressures and therefore ice thicknesses. The method is here applied to Bláhnúkur, a subglacially erupted rhyolitic edifice in Iceland. A decrease in water content from ∼0.7 wt.% at the base to ∼0.3 wt.% at the top of the edifice suggests that the ice was 400 m thick at the time of the eruption. As Bláhnúkur rises 350 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 83 publications
(201 reference statements)
0
19
0
Order By: Relevance
“…Dixon and Clague, 2001;Tuffen et al, 2010). The same methodology was undertaken as with samples from Bláhnúkur in Owen et al (2012) where a detailed description of the analytical procedure can be found.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Dixon and Clague, 2001;Tuffen et al, 2010). The same methodology was undertaken as with samples from Bláhnúkur in Owen et al (2012) where a detailed description of the analytical procedure can be found.…”
Section: Methodsmentioning
confidence: 99%
“…Various palaeo-pressure conditions were modelled based on the water solubility-pressure relationships given by VolatileCalc (Newman and Lowenstern, 2002). See Tuffen et al (2010) and Owen et al (2012) for more information on this technique.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 2) as an effective tool for inferring palaeo-ice thicknesses (Tuffen et al, 2010;Owen et al, 2012). Analyses by the CheMin XRD instrument on the NASA Mars Curiosity rover indicated that 27±14% of the local regolith was composed of amorphous component, indicative of basaltic volcanic glass (Bish et al, 2013).…”
Section: Sequestered Volatiles In Volcanic Glassmentioning
confidence: 99%